[1-(2,5-Dichloroanilino)-5-methyl-1H-1,2,3-triazol-4-yl]methanol - Cunha, Anna C.; Jordão, Alessandro K.; Souza, Maria C. B. V. de; Ferreira, Vitor F.; Almeida, Maria C. B. de; Wardell, James L.; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
In the title compound, C10H10Cl2N4O, the hydroxy group and benzene ring are disposed to opposite sides of the central 1,2,3-triazolyl ring. The dihedral angle between the five- and six-membered rings is 87.51 (12)°, and the C-O bond of the hydroxy group lies almost normal to the plane of the 5-membered ring [N-C-C-O = -93.2 (2)°]. An intramolecular amino-N-H...Cl hydrogen bond is noted. In the extended structure, supramolecular layers in the ab plane are formed via hydroxy-O-H...N(ring) and amine-N-H...O(hydroxy) hydrogen bonds. The layers are connected along the c axis by [pi]-[pi] contacts between benzene rings [inter-centroid distance = 3.7789 (13) Å] and by C-Cl...[pi] interactions.